My Understanding of the Origin and Prevention of New Coronavirus Disease - Chunwu, Sun (Advances in Social Sciences Research Journal, 2023)
My work on the "Origin and Prevention of New Coronavirus Disease" must be thoroughly and systematically studied. It must not be mistaken for a certain intermediate host to evolve into a new coronavirus disease. Or the challenge is that the time and scale of each outbreak are unpredictable, and the infectivity is difficult to eliminate the misjudgment. Using measures such as closing the city and roads to limit the scope of the "new coronavirus" contagion campaign may be a bit sloppy, and it will not outweigh the gains. The following first discusses the origin and prevention of the "new coronavirus" disease in detail, and establishes effective universal epidemic prevention to recapture the economic losses in the epidemic.